(untitled) (قضايا سياسية, 2023)
It is Wall Known that Water is the main determinant of the various development programs in any country, as it reflects the investment pattern of cultivated land and the possibilities of expanding it according to the amount of available water: It is also an indicator of industrial quality that relies on water for its production. The main source of water in Iraq is surface water represented by the Tigris and Euphrates rivers, which flow from outside its regional borders, which put Iraq in front of a weakness in terms of the connection of its water resources to several countries, especially Turkey. As the amount of water imports for the two rivers began to decrease a lot starting from the nineties of the twentieth century, this is due to the policy of building dams and water projects at the sources of the two rivers, such as: (Al - GAP). Which hydrogen changes for the two rivers, represented by a decrease in the amount of water incoming, natural rivers. Also, despite the existence of many agreements that deal with regulating the use of water in the two rivers between the three riparian countries. However, Turkey has pursues, through all negotiations related to this file, to relate and empower this case with other cases, including political, security and economic ones, with the aim of obtaining the largest possible gains in its favor regarding this issue, which urges the Iraqi government to realize the seriousness of this file, and to act accordingly. We have seen that the political solution lies in following a specific strategy with multiple and advanced techniques.